Long Term Gene Expression in Human Induced Pluripotent Stem Cells and Cerebral Organoids to Model a Neurodegenerative Disease - Nassor, Ferid; Jarray, Rafika; Biard, Denis S. F.; Maïza, Auriane; Papy-Garcia, Dulce; Pavoni, Serena; Deslys, Jean-Philippe; Yates, Frank (Frontiers in Cellular Neuroscience, 2020)
Human brain organoids (minibrains) are self-organized three-dimensional (3D) neural tissues which can be derived from reprogrammed adult cells and maintained for months in culture. These 3D structures hold great potential for the modeling of neurodegenerative diseases and pave the way for personalized medicine. However, as these 3D brain models can express the whole human genetic complexity, it is critical to have access to isogenic minibrains that only differ on specific and controlled genetic variables. Genetic engineering based on retroviral vectors is incompatible with the long-term modeling needed here and implies a risk of random integration while methods using CRISPR-Cas9 are still complex to adapt to stem cells. We demonstrate in this study that our strategy relying on an episomal plasmid vector derived from the Epstein-Barr virus offers a simple and robust approach to avoid the remaining caveats of minibrain models. For this proof-of-concept, we used a normal tau protein with a fluorescent tag and a mutant genetic form (P301S) leading to Fronto-Temporal Dementia. We obtained isogenic cell lines stable for more than 30 passages expressing either forms. We show that the presence of the plasmid in the cells does not interfere with the minibrain differentiation protocol and we obtain the development of a pathologically relevant phenotype in cerebral organoids, with a pathological hyperphosphorylation of the tau protein. Such a simple and versatile genetic strategy opens the full potential of human organoids to contribute to disease modeling, personalized medicine and testing of therapeutics.